Single-Stage Surgical Procedure for Patients with Primary Esophageal and Lung Cancers - Lianyong, Jiang; Fengqing, Hu; Xiao, Xie; Xuefeng, Zhang; Rui, Bi (The Thoracic and Cardiovascular Surgeon, 2023)
Background The aim of this study was to evaluate the safety and feasibility of simultaneous surgery for patients with primary esophageal and lung cancers.Methods Patients with primary esophageal and lung cancers who underwent simultaneous surgical procedures between January 2016 and January 2022 were retrospectively analyzed. The data of patients who underwent esophagectomy and lobectomy (group EL) were compared with those of patients who underwent esophagectomy and sublobar resection (group ES).Results A total of 21 patients were included with an average age of 64.62 ± 5.24 years. Group EL contained 8 patients and group ES contained 13 patients. All procedures were completed uneventfully with a mean operative time of 251.19 ± 66.93 minutes. Pulmonary complications occurred in six (28.57%) patients. Other complications included anastomotic leakage in 1 patient, pleural effusion requiring drainage in 8 patients, atrial fibrillation in 2 patients, and incision infection in 1 patient. All patients were followed up for 30.23 ± 21.82 months. During the follow-up period, nine patients had a recurrence of cancer and died of tumor progression, and one patient died of a tracheothoracogastric fistula. Complications and mortality in group EL did not increase when compared to those in group ES.Conclusion It is safe and feasible to perform a single-stage surgical procedure for patients with primary esophageal and lung cancers. Simultaneous esophagectomy and lobectomy did not increase postoperative complications or mortality compared with esophagectomy and sublobar resection.
Keywords: esophageal surgery; lung cancer treatment (surgery medical); outcomes (includes mortality morbidity); surgery; complications